Distribution of mistletoes in the Central Valley of Chile - Tainter, F.H.; French, D.W. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
In the Central Valley of Chile, two genera of Viscaceae were identified parasitizing five host species: six species of Loranthaceae on thirty-six host species and four species of Myzodendraceae on eight hosts; most of them Nothofogus. The parasitic plants were collected in the field and compared with samples from the herbarium of the National Museum of Chile. Most of the parasitic plants are endemic to the native forest and their presence is either dispersed or localized; however, some intensely attacked host species such as Populus spp. and Robinia pseudoacacia are introduced.